The ten commandments [videorecording (DVD)] - DeMille, Cecil B. (Cecil Blount), 1881-1959; Heston, Charlton; Brynner, Yul; Baxter, Anne; Robinson, Edward G., 1893-1973 (Paramount DVD, 2006)
To escape the edict that condemned all first-born Hebrew males by Egypt's Pharoah, Rameses I, the infant Moses is set adrift on the Nile in a reed basket. Saved by the pharaoh's daughter Bithiah, he is adopted by her and brought up in the court of her brother, Pharaoh Seti. Moses gains Seti's favor and the love of the throne princess Nefertiri. He also gains the hatred of Seti's son, Rameses. When his Hebrew heritage is revealed, Moses is cast out of Egypt, and makes his way across the desert where he marries, has a son and is commanded by God to return to Egypt to free the Hebrews from slavery. In Egypt, Moses's fiercest enemy proves to be not Rameses, but someone near to him.